PENGARUH KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PERSEPSI KUALITAS LAPORAN KEUANGAN SATUAN KERJA PERANGKAT DAERAH (SKPD) DI KABUPATEN BONDOWOSO - Ulfa, Rofiana; Sularso, Raden Andi; Sayekti, Yosefa (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: This study aimed to analyze the influence of the competencies of human resources that consisted of knowledge, skill, and attitude on the perceived quality of the financial statements generated by the administrators of Regional Work Unit (SKPD) of the Government of Bondowoso. The study was conducted in 58 (fifty eight) SKPDs in Bondowoso Regency Government.The sample consisted of 102 (one hundred and two) civil servants working in finance and planning department that responsible for completing the financial statements of SKPD. Data were analyzed using Structural Equation Modelling (SEM). Results showed that knowledge and attitude have significant effects on the perceived quality of financial statements while skill has no significant effect on the perceived quality of the financial statements. Keywords: Knowledge, Skill, Attitude, Perception, and Quality of Financial Statements.